Ion mobility spectrometry of N-methylimidazole and possibilities of its determination - D. A. Aleksandrova; T. B. Melamed; E. P. Baberkina; A. A. Fenin; E. S. Osinova; А. E. Kovalenko; R. V. Yakushin; Yu. R. Shaltaeva; V. V. Belyakov; D. I. Zykova (Тонкие химические технологии)
Objectives. To determine the ion mobility of N-methylimidazole, establish the structure of ions corresponding to characteristic signals, and determine the detection limit of N-methylimidazole on the ion-drift detector Kerber.Methods. Ion mobility spectrometry was used to study the ionization processes. The enthalpies of the reactions of monomer and dimer ions were calculated in the ORCA 4.1.1 software by the B3LYP density functional method with a set of basic functions 6-31G (d, p).Results. The drift time and ion mobility values of N-methylimidazole were determined. A method for mathematical processing of spectra and a program for its implementation was developed. The changing peculiarities of the ion mobility spectrum during measurement at a given time were studied. According to the interpretation of the spectrum signals, the structure of the generated ions was proposed, and the enthalpies of ion formation were determined.Conclusions. The characteristic signal of the N-methylimidazole ion protonated at the nitrogen atom of the pyridine type was revealed. It was found that two signals in the ion mobility spectra of N-methylimidazole correspond to the presence of the monomer and dimer ions. The detection limit of N-methylimidazole on the ion-drift detector Kerber was determined, amounting to 3 pg.